La no caducidad de la potestad de declaratoria de lesividad de los actos administrativos referentes a los Bienes Públicos - Fares Sarmiento, Francisco José (2020)
The present investigation presented under the thesis modality refers to a legal problem that deserves to be transformed to solve and overcome the socio-legal problem identified in the article 116 of the Organic Administrative Code, which prescribes on the expiration of the revocation power of Favorable acts if three years have elapsed since the notification of the administrative act, which limits that the highest authority of the public institution when encountering administrative acts contrary to the public interest and that have passed more than three years, can never declare those injuries harmful administrative acts when they are related to the protection of public use assets, this should be understood as an attempt against the inherent control of legality of administrative acts that are born into legal life in the Public Administration of the Republic of Ecuador. Consequently, it is necessary to protect the assets of the State against bad actions by the public administration and therefore it is necessary to reform article 116 of the Organic Administrative Code, stipulating that the power to declare lesividad regarding the protection of assets in the public use it will not be subject to expiration.